Parkinson’s Disease Follow Up Self-Assessment Scale (Medico Legal Update, 2020)
Parkinson’s disease is a neurodegenerative progressive disorder end with independency for many years atlate life, leading to great burden on patient and family life. The available treatment is symptomatic focusedon improving life quality of the patient and it’s in need for good communication with the physician.So far there is no easy and practical way for follow up, thus we’ve designed the Parkinson’s disease followup self-assessment scale aiming to detect ON and OFF time, it’s include PD manifestations, medications andmedications adverse effects filled out by the patient family at home in order to mailing it to the physician,and intend to testing it by comparing the performance of patient family with expert staff in using the scale athospital for 24 hours. Then enquiring about difficulty of using the same scale at home.A 44 PD patient were completed the study. All items accuracy filling out was 93.4% in compare to expertstaff. Its mean degree of difficulty was 4/10 and among patients families only 29.54% consider it difficult touse. The ON and OFF time was detected precisely in 92.2% by follow up physician. The proposed scale isprecise in detection ON an OFF time and not difficult to use.